Integrated Language Learning in Elementary School - Ferril Muzaki (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Language is not only from words, but also meaning behind those words. In discourse, there are two components: intra linguistics and extra linguistics. Intra-linguistic component means discourse build from word to word, phrase to phrase, sentences to sentences, paragraph to paragraph at the end it becomes discourse. Extra linguistics competences have some components, settings, purposes, and others component when the text is composed. I will explain how to teach discourse in teaching reading. First, teacher gives questions to open the class; the question should open students' background knowledge about subject at that day. At that stage, teachers should try to raise students' curiosity at that topic. Teachers should ask students opinion about the topic. After that stage, the teacher gives students an up-to-date material close to students' real life. In this stage, students read it by scanning and skimming. The next step, teacher asks students to analyze structure (grammar), vocabulary, and how author developing ideas their composition.